The First 100 Days Stormfront Responds to Obama's Presidency. - Dentice, Dianne; Williams, James L. (Theory in Action, 2010)
This paper is a follow-up analysis of an article by Dentice and Williams (2008) that tracked the presidential campaign on Stormfront.org prior to the election of our nation's first African American president. Stormfront, an online discussion forum for people who self-identify as “white nationalists,” is an important venue for extremist political opinions. Five discussion forums reveal reactions to and opinions about Obama's election and his first 100 days in office. Findings reveal a deep distrust of both the government and politicians. Discussants resort to anti-Semitism in an effort to explain the Òbama crisis.' Analysis of Stormfront post election discussions offers insights into how this particular segment of American society views the most historic presidential election in our nation's history and why self-identified white nationalists feel the shift in power threatens their separatist version of the American dream. [Article copies available for a fee from The Transformative Studies Institute. E-mail address: journal@transformativestudies.org Website: http://www.transformativestudies.org ©2010 by The Transformative Studies Institute. All rights reserved.].